Question
upstudy study bank question image url

Use the four-step process to find \( f^{\prime}(x) \) and then find \( I^{\prime}(1), I^{\prime}(2) \), and \( f^{\prime}(3) \) \( f^{f}(x)=2 x^{2}-5 x+3 \) \( f^{\prime}(x)=\square \) \( f^{\prime}(1)=\square \) (Type an integer or a simplified fraction.) \( f^{\prime}(2)=\square \) (Type an integer or a simplified fraction.) \( f^{\prime}(3)=\square \) (Type an integer or a simplified fraction.)

Ask by Luna Goodwin. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( f^{\prime}(x) = 4x - 5 \) \( f^{\prime}(1) = -1 \) \( f^{\prime}(2) = 3 \) \( f^{\prime}(3) = 7 \)

Solution

Sure, let's go through the four-step process to find the derivative \( f^{\prime}(x) \) of the function \( f(x) \) and then evaluate it at specific points. ### Step 1: Understand the Function It appears there might be a typographical error in the given function notation. Assuming the function is: \[ f(x) = 2x^2 - 5x + 3 \] ### Step 2: Find the Derivative \( f^{\prime}(x) \) To find the derivative of \( f(x) \), we'll apply the basic differentiation rules: - The derivative of \( x^n \) is \( n x^{n-1} \). - The derivative of a constant is 0. So, \[ f'(x) = \frac{d}{dx}(2x^2) - \frac{d}{dx}(5x) + \frac{d}{dx}(3) \] \[ f'(x) = 4x - 5 + 0 \] \[ f'(x) = 4x - 5 \] ### Step 3: Evaluate \( f^{\prime}(x) \) at Specific Points 1. **At \( x = 1 \):** \[ f'(1) = 4(1) - 5 = 4 - 5 = -1 \] 2. **At \( x = 2 \):** \[ f'(2) = 4(2) - 5 = 8 - 5 = 3 \] 3. **At \( x = 3 \):** \[ f'(3) = 4(3) - 5 = 12 - 5 = 7 \] ### Summary of Results \[ \boxed{ \begin{aligned} f'(x) &= 4x - 5 \\ f'(1) &= -1 \\ f'(2) &= 3 \\ f'(3) &= 7 \\ \end{aligned} } \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To find \( f^{\prime}(x) \) from the function \( f(x) = 2x^{2} - 5x + 3 \), we'll follow the four-step process of differentiation: 1. **Identify the Function**: \( f(x) = 2x^{2} - 5x + 3 \). 2. **Apply the Power Rule**: The derivative of \( x^{n} \) is \( n \cdot x^{n-1} \). Thus: - The derivative of \( 2x^2 \) is \( 2 \cdot 2x^{2-1} = 4x \). - The derivative of \( -5x \) is \( -5 \). - The derivative of a constant (3) is \( 0 \). 3. **Combine the Results**: So, \( f^{\prime}(x) = 4x - 5 \). 4. **Conclusion**: Therefore, \( f^{\prime}(x) = 4x - 5 \). Now to find \( f^{\prime}(1) \), \( f^{\prime}(2) \), and \( f^{\prime}(3) \): - \( f^{\prime}(1) = 4(1) - 5 = 4 - 5 = -1 \). - \( f^{\prime}(2) = 4(2) - 5 = 8 - 5 = 3 \). - \( f^{\prime}(3) = 4(3) - 5 = 12 - 5 = 7 \). So, the final answers are: - \( f^{\prime}(x) = 4x - 5 \) - \( f^{\prime}(1) = -1 \) - \( f^{\prime}(2) = 3 \) - \( f^{\prime}(3) = 7 \)

Related Questions

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy